2019
DOI: 10.1097/olq.0000000000001083
|View full text |Cite
|
Sign up to set email alerts
|

Patients Are Willing to Wait for Rapid Sexually Transmitted Infection Results in a University Student Health Clinic

Abstract: We examined the acceptability and feasibility of using a 30-minute chlamydia/gonorrhea test in a student health clinical setting. One hundred eight students were enrolled and 89.4% were willing to wait up to 20 minutes beyond the conclusion of their routine visit. The average amount of time added per clinic visit was less than 11 minutes. Patient and staff satisfaction were high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Finally, in the United States, Gettinger and colleagues used the binx health io assay, a 30-minute test, and sample-first approach that minimized wait times, as the sample testing began before patient interaction with a clinical provider. 26 In this highly efficient university student health clinic, waiting for results added an average of 11 minutes to the total clinical visit. In contrast to the Harding-Esch findings, in this study, 83% of the 108 participants were willing to wait for their results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in the United States, Gettinger and colleagues used the binx health io assay, a 30-minute test, and sample-first approach that minimized wait times, as the sample testing began before patient interaction with a clinical provider. 26 In this highly efficient university student health clinic, waiting for results added an average of 11 minutes to the total clinical visit. In contrast to the Harding-Esch findings, in this study, 83% of the 108 participants were willing to wait for their results.…”
Section: Resultsmentioning
confidence: 99%
“… 16 At the patient level, new screening approaches that lower diagnostic running time and decrease the time between receiving results and treatment can help to improve patient motivation to seek testing. 15 , 20 , 21 , 26 When implementing new screening processes, patient characteristics have a large effect on acceptance and willingness to seek testing. Studies in this review showed that self-sampling is generally acceptable to patients.…”
Section: Discussionmentioning
confidence: 99%
“…The binx health io CT/NG has been implemented in a small number of clinical settings, however, available reports show the test being implemented in research-use only scenarios in the USA [ 43 , 44 ] and publications (to-date of this review) reporting implementation in the UK do not report clinical and other health-related outcomes [ 45 ]. The Cepheid CT/NG GeneXpert has been implemented and evaluated for multiple outcomes measures in many settings around the world.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 4 , in addition to the Cepheid CT/NG GeneXpert studies included in Table 3 , we report on a wider literature of stakeholder values for implementation of POCTs, including reports of the binx health io CT/NG. Studies reporting implementation of the binx CT/NG in a sexual health specialist service and a University student health clinic (outreach service) in the USA were restricted to implementation without results delivery; at the time of the studies the test was not yet FDA approved [ 43 , 44 , 73 ]. Publication of a UK-based project tracing implementation into routine care did not include assessment of clinical outcomes [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation